2020
DOI: 10.3389/fphar.2019.01646
|View full text |Cite
|
Sign up to set email alerts
|

Antitumor Effects of Trimethylellagic Acid Isolated From Sanguisorba officinalis L. on Colorectal Cancer via Angiogenesis Inhibition and Apoptosis Induction

Abstract: Previous studies have demonstrated that tannin could inhibit the proliferation and angiogenesis of cancer cells. However, the mechanism(s) associated with its antitumor effect remains unclear. Here, we investigated the effects of 3,3',4'-trimethylellagic acid (TMEA), a tannin compound isolated from Sanguisorba officinalis L., on the proliferation, angiogenesis, and apoptosis in cancer cells, as well as the underlying mechanism(s) related to its antitumor activity. TMEA was isolated from Sanguisorba officinalis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 49 publications
(53 reference statements)
0
19
0
Order By: Relevance
“…It was reported that a hot water preparation made of a single herb (SO) has excellent antitumor effect in human oral cancer cells ( Shin et al, 2012 ). Moreover, triterpenoids and tannins isolated from the roots of SO have been shown promising antitumor effects in several cancer researches ( Liu et al, 2005 ; Bai et al, 2019 ; Li et al, 2019 ). Notably, it was reported recently that Ziyuglycoside II, a major active compound of SO, markedly impaired HepG2 proliferation, migration and invasion, by blocking EGFR/NF-kB signaling ( Liao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that a hot water preparation made of a single herb (SO) has excellent antitumor effect in human oral cancer cells ( Shin et al, 2012 ). Moreover, triterpenoids and tannins isolated from the roots of SO have been shown promising antitumor effects in several cancer researches ( Liu et al, 2005 ; Bai et al, 2019 ; Li et al, 2019 ). Notably, it was reported recently that Ziyuglycoside II, a major active compound of SO, markedly impaired HepG2 proliferation, migration and invasion, by blocking EGFR/NF-kB signaling ( Liao et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, TCM has been widely used as a pool filed with abundant novel therapeutic agents for approximately 63–83% of patients with breast cancer, owing to its favorable efficacies, accessible availability, and limited adverse effects ( Liu et al, 2019 ; Yang et al, 2019 ). Sanguisorba officinalis L (SA, Chinese name as Di Yu; The voucher number/barcode 2,896,446) is traditionally prescribed for cancer prevention and treatment that putatively works by reducing blood toxicity and enhancing immunity in patients ( Bai et al, 2019 ). In our early study, we found SA exerted an obvious inhibitory effect on breast cancer angiogenesis, which is known to represent the basis of tumor growth, invasion, and metastasis ( Wang et al, 2012b ).…”
Section: Introductionmentioning
confidence: 99%
“…Gallic acid, a major compound of phenols in Sanguisorba officinalis L., could bind to ferroptosis-related targets and regulate the expression of corresponding proteins; ferroptosis inhibitors reversed the experimental results, improving CRC by regulating ferroptosis [24]. Another compound named 3,3 ,4trimethylellagic acid (TMEA), a tannin compound isolated from Sanguisorba officinalis L., executed its anti-cancer activity by inducing apoptosis and inhibiting angiogenesis in CRC cells via the apoptotic and VEGF/PI3K/AKT/mTOR pathways [25]. A type of tannin compound named 1,4,6-Tri-O-galloyl-beta-d-glucopyranose significantly inhibited the Wnt/beta-catenin signaling pathway, up-regulated the protein levels of cleaved caspase-3 and cleaved PARP, as well as the ratio of Bax/Bcl-2 proteins in HT29 cell [26].…”
Section: Discussionmentioning
confidence: 99%